Multiphasic Screening as a Diagnostic Method in Preventive Medicine - Collen, Morris F. (Methods of Information in Medicine, 1965)
An automated multiphasic screening program has been described utilizing automated and semi-automated electronic and mechanical equipment to rapidly provide comprehensive, quantitative, and precise testing for a large number of diseases.The data processing system and computer requirements of the program have been reviewed. The program incorporates a statistical method which automatically determines the likelihood of the presence or absence of selected diagnoses according to pre-determined sensitivity and specificity criteria.